TikTok, Instagram and Facebook Impact to the Hotels in the United Kingdom, Ireland and Spain - Timotius A Racmat; Irma M Nawangwulan; Samuel PD Anantadjaya; Deby C Borosi; Pikat AR Muqaddasah; DC Ethan Samuel; Daniella CE Samuel; Brian McNerney (Sekolah Tinggi Manajemen IPMI, 2025)
This study examines the influence of 3 major social media platforms—TikTok, Instagram, and Facebook—on hotel selection among Zennial travelers (Millennials and Gen Z) across the UK, Ireland, and Spain. As tourism in these regions becomes increasingly shaped by digital engagement, social media has evolved into a central driver of travel inspiration, evaluation, and booking behavior. Using the Theory of Planned Behavior (TPB), this study explores how attitudes (shaped by visual appeal and influencer credibility), subjective norms (driven by peer interactions, likes, shares, and group discussions), and perceived behavioral control (influenced by accessible booking links, price transparency, and informational clarity) contribute to travelers’ booking intentions. The findings reveal that TikTok primarily drives initial desire and discovery, Instagram strengthens emotional connection and expectation-setting, and Facebook provides informational security that supports final booking decisions. Collectively, these platforms form an interconnected digital pathway that guides travelers from inspiration to confirmation across the UK, Ireland, and Spain. The research underscores the need for hospitality marketers to adopt cross-platform strategies that integrate authenticity, visual storytelling, and community-based trust to effectively influence the modern travel consumer.